ELECTRICAL CONDUCTIVITY TEST ON ANDROPOGON GRASS SEEDS (REMUNOM, 2026)
Determining the physiological quality of Andropogon grass seeds is still hampered by the lack of standardized tests for this species. This study aimed to propose a methodology for the electrical conductivity test in Andropogon grass seeds, considering different water volumes and soaking periods. Two seed lots of Andropogon grass, cultivar Planaltina, were used. Initially, water content, germination, root protrusion, first germination count, seedling emergence, emergence speed index, and seedling length were determined. The electrical conductivity test was conducted using different water volumes (50 and 75 mL) and soaking periods (2, 4, 6, 8, 10, 12, 14, 16, 18, and 24 hours), with five replicates of 50 seeds. Electrical conductivity readings were taken using a conductivity meter, and the results were expressed in μS cm-1 g-1. Soaking period and water volume influenced the electrical conductivity values of the seed lots. The electrical conductivity test performed with 8 hours of soaking in 75 mL of distilled water showed potential for evaluating the vigor of Andropogon grass seeds, indicating the possibility of differentiating seed lots and contributing to faster seed quality assessment.